Peran Orang Tua terhadap Remaja Putus Sekolah di Jorong Kapuah Nagari Sumani Kabupaten Solok - Susanti, Fitria; Syam, Hidayani (YASIN, 2024)
Out-of-school teenagers are teenagers who cannot continue or stop going to school before completing primary and secondary education. This is caused by special conditions experienced by teenagers, such as a lack of parental guidance in motivating them to go to school. Basically, the impact of dropping out of school is a lack of insight or knowledge possessed by teenagers, the future of teenagers is unclear. This type of research is descriptive qualitative research which describes the role of parents in teenagers dropping out of school in Jorong Kapuah Nagari Sumani, Solok Regency. In collecting data, researchers used observation and interview techniques, while to analyze it, researchers used data reduction, data presentation and data verification steps. The results of the research show that there are several roles of parents for teenagers who have dropped out of school in Jorong Kapuah Nagari Sumani, Solok Regency, namely the role of parents for teenagers who have dropped out of school, including, for teenagers who have dropped out of school, parents as mentors, for teenagers who have dropped out of school, parents as a facilitator and for teenagers who have dropped out of school, parents as motivators for teenagers who have dropped out of school in Jorong Kapuah Nagari Sumani, Solok Regency.